Self-Care Behavior Regarding Hypertension in Elderly Patients in Lahore - Nafees, Nabila; Ghani, Mansoor; Nafees, Neelam; Kausar, Samina (Biological and Clinical Sciences Research Journal, 2025)
Hypertension is a major contributor to global morbidity and mortality, particularly among the elderly in low- and middle-income countries. While self-care behaviors are essential in blood pressure control, limited evidence exists regarding self-care practices among elderly hypertensive patients in Pakistan. Objective: To assess self-care behavior and its associated determinants among elderly hypertensive patients attending tertiary hospitals in Lahore, Pakistan. Methods: A descriptive cross-sectional study was conducted among 200 elderly hypertensive patients recruited from outpatient departments of three tertiary hospitals in Lahore from January to December 2024 using non-probability purposive sampling. A culturally adapted self-care behavior questionnaire assessing six domains was administered. Anthropometric and clinical data were recorded following standardized protocols. Descriptive and inferential statistics were applied, including Chi-square tests and independent t-tests, with significance set at p ≤ 0.05. Results: Participants had a mean age of 65.3 years, and 58.5% were male. Most respondents lived with family (89.5%), and 78.5% perceived their health as fair or poor. Overall, only 22.5% of participants demonstrated adequate self-care behavior. Physical activity (78.5%) and smoking avoidance (77%) showed acceptable adherence, whereas medication adherence (22%), weight management (26%), salt restriction (38%), and stress control (32%) remained suboptimal. Self-care behavior was significantly associated with living status, marital status, education, income, and self-rated health (p<0.05), but not with gender or treatment duration. Patients with inadequate self-care had significantly higher systolic blood pressure, diastolic blood pressure, and BMI than those with adequate self-care (p<0.001). Conclusion: Elderly hypertensive patients in Lahore exhibit poor overall self-care behavior, particularly in dietary control, stress management, and treatment adherence. Social and economic determinants strongly influenced self-care performance, and inadequate self-care was associated with worse clinical indicators. Tailored educational initiatives, family support mobilization, and community-based self-management programs are urgently needed to improve hypertension outcomes in this high-risk population.